2017
DOI: 10.1016/j.nbt.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Mineralisation of 14C-labelled polystyrene plastics by Penicillium variabile after ozonation pre-treatment

Abstract: Large amounts of polystyrene (PS), one of the most widely used plastics in the world, end up in the environment through industrial discharge and littering, becoming one of the major components of plastic debris. Such plastics, especially the small-sized microplastics and nanoplastics, have received increasing concerns in terms of their potential environmental risks. Feasible approaches for the degradation of PS in waste materials and in the environment are highly desirable. Physicochemical pretreatments of PS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(27 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…However, because of the biodegradation decalogue (Alexander 1975), studying these steps remains challenging for microplastics. Highly sensitive approaches, such as mineralization experiments of 14 C-labeled synthetic polymers in marine in situ conditions [comparable to the 14 C-polystyrene polymer in vitro cultivation experiment using the fungus Penicillium variabile (Tian et al 2017)], are essential to recognize the lifetime of microplastics in the ocean.…”
Section: Biodegradation Of Microplastics In the Oceanmentioning
confidence: 99%
“…However, because of the biodegradation decalogue (Alexander 1975), studying these steps remains challenging for microplastics. Highly sensitive approaches, such as mineralization experiments of 14 C-labeled synthetic polymers in marine in situ conditions [comparable to the 14 C-polystyrene polymer in vitro cultivation experiment using the fungus Penicillium variabile (Tian et al 2017)], are essential to recognize the lifetime of microplastics in the ocean.…”
Section: Biodegradation Of Microplastics In the Oceanmentioning
confidence: 99%
“…Furthermore, pretreatment with ozone gas boosted mineralization of PS films from 0.01% to 0.15%. Gel permeation chromatography (GPC) showed a decrease in molecular size, confirming the ability of the fungus to biodegrade PS ( Tian et al, 2017 ). Mushroom Gloeophyllum trabeum , which is a lignocellulose degrader, showed that it managed to reduce the average molecular mass ( M n ) of the soluble polystyrene sulfonate (PSS) up to 80% after 20 days.…”
Section: Microbial and Enzymatic Degradation Of Plasticsmentioning
confidence: 87%
“…An additional source comprises bacteria and fungi already deposited in culture collections [ 157 ]. All major synthetic polymers have species reported to degrade them, for instance PE [ 158 , 159 ], PET [ 160 , 161 ], PP [ 162 ], PS [ 163 ], PU [ 164 ] and PVC [ 165 ]. However, the strength of evidence for degradation varies by plastic type.…”
Section: Mitigation Of Plastic Pollution By the Environmental Microbiomementioning
confidence: 99%